2016
DOI: 10.7555/jbr.30.20150131
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies in Alzheimer's disease: potential biomarkers, pathogenic roles, and therapeutic implications

Abstract: Alzheimer’s disease (AD) is a prevalent and debilitating neurodegenerative disorder in the elderly. The etiology of AD has not been fully defined and currently there is no cure for this devastating disease. Compelling evidence suggests that the immune system plays a critical role in the pathophysiology of AD. Autoantibodies against a variety of molecules have been associated with AD. The roles of these autoantibodies in AD, however, are not well understood. This review attempts to summarize recent findings on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 108 publications
0
27
0
Order By: Relevance
“…An autoantibody screening study identified autoantibodies in CSF that target glia-derived nexin, actin-interacting proteins, metalloproteinase inhibitor 2, quinone oxidoreductase, inositol trisphosphate receptor 1, and endoplasmic reticulum calcium ATPase 2 [ 43 ]. The levels of autoantibodies targeting ATP synthase, angiotensin II type 1, and 5-hydroxytryptamine also are altered in AD [ 44 ]. The concentration of IgM and IgG autoantibodies targeting alpha B-crystallin is increased in AD patients [ 45 ].…”
Section: Role Of Igs In Admentioning
confidence: 99%
See 1 more Smart Citation
“…An autoantibody screening study identified autoantibodies in CSF that target glia-derived nexin, actin-interacting proteins, metalloproteinase inhibitor 2, quinone oxidoreductase, inositol trisphosphate receptor 1, and endoplasmic reticulum calcium ATPase 2 [ 43 ]. The levels of autoantibodies targeting ATP synthase, angiotensin II type 1, and 5-hydroxytryptamine also are altered in AD [ 44 ]. The concentration of IgM and IgG autoantibodies targeting alpha B-crystallin is increased in AD patients [ 45 ].…”
Section: Role Of Igs In Admentioning
confidence: 99%
“…As the number of people developing AD is expected to increase, we need to develop low-cost and patient-friendly diagnostic techniques based on blood biomarkers. Autoantibodies are one candidate blood biomarker; indeed, anti-Aβ and -tau protein antibodies have been used as biomarkers [ 44 ]. Autoantibodies targeting Aβ have been studied by many groups.…”
Section: Role Of Igs In Admentioning
confidence: 99%
“…Various novel blood- and CSF-based biomarkers for AD have been proposed in recent years. These include (1) neuroinflammatory markers such as reactive oxygen species (ROS), cytokines, chemokines, astrocytes, and activated microglia; (2) proinflammatory molecules such as interleukins (ILs), interferons (IFNs), and tumour necrosis factors (TNFs); (3) autoantibodies; (4) trace elements such as copper, zinc, iron; (5) fatty acids, sphingolipids, ceramides; (6) micro-RNAs; (7) circulating nanocomponents; and others [ 26 , 27 , 28 , 29 , 30 , 31 ]. Alternatively, non-invasive neuroimaging techniques such as computerized tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography (PET) offer structural and functional information about the brain, which may be able to support a diagnosis of dementia, but only in the later stages when brain shrinkage is evident.…”
Section: Introductionmentioning
confidence: 99%
“…A distinct proportion of patients with dementia are immunotherapy-responsive [ 16 ], which indicates a dementia-related autoimmune background. Target-destructing autoantibodies, many of which are documented in [ 1 , 2 ], were preferentially discussed in this context. However, there is a new class of functional autoantibodies which bind to GPCRs.…”
Section: Discussionmentioning
confidence: 99%
“…Dementia in general and particularly Alzheimer’s disease are seen increasingly in association with an autoimmune background that could be causatively or supportively involved in the pathogenesis. In addition to the variety of autoantibodies (AABs) detected in patients with dementia and suggested to be pathogenic players, biomarkers and treatment targets such as those summarized in [ 1 , 2 ], there is a new class of autoantibodies, the so-called functional autoantibodies that are directed against G-protein coupled receptors (GPCRs; GPCR-AABs) which are increasingly seen as pathogenic players. For GPCR-AABs and the related diseases, which can be named “functional autoantibody disease”, basics, diagnostics and treatment strategies are summarized in [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%